The concept of state policy for enterprise development and its features in the context of european integration - Zabashta, Yevhen (P.A. Persona e Amministrazione, 2023)
The study aims to substantiate and deepen the theoretical foundations of the state policy for enterprise development in the context of European integration. The methodological framework of the study involved the following methods: analysis and formalization, logical generalization, abstract-logical method, and induction and deduction. Analysis and formalization provided for determining the essence of such concepts as entrepreneurship, small and medium-sized enterprises, and state policy for enterprise development. Logical generalization involved defining and formulating the scientific principles of state policy for enterprise development. Abstract-logical method ensured theoretical generalization and drawing the conclusions of the study. Methods of induction and deduction helped define the issue under the study and clarify its subject. The essence of small and medium-sized enterprises in Ukraine is analyzed. In order to develop and improve the state policy for enterprise development in Ukraine, which has been granted the status of a candidate for EU membership, the authors of this article suggested legal, organizational, regulatory, and institutional changes that would promote the development of entrepreneurial activity and adaptation to the European space in the future. Entrepreneurship development requires attracting investment and sufficient financing from the state and international investors. The factors influencing the state policy for enterprise development and growth of small and medium-sized enterprises were analyzed. The enterprise development strategy in Ukraine was examined. The authors studied enterprises in Ukraine and suggested the mechanisms of the state policy for their development.